Distinct genome‐wide alternative polyadenylation during the response to silicon availability in the marine diatom Thalassiosira pseudonana. (1st April 2019) - Fu, Haihui; Wang, Peng; Wu, Xiaohui; Zhou, Xiaoxuan; Ji, Guoli; Shen, Yingjia; Gao, Yahui; Li, Qingshun Q.; Liang, Junrong
Summary: The post‐transcriptional regulation involved in the responses of diatoms to silicon is poorly understood. Using a poly(A)‐tag sequencing (PAT‐seq) technique that interrogates only the junctions of 3′‐untranslated region (UTR) and the poly(A) tails at the transcriptome level, a comprehensive comparison of alternative polyadenylation (APA) was performed to understand the role of post‐transcriptional regulation in various silicon‐related cellular responses for the marine diatom Thalassiosira pseudonana . In total, 23 701 poly(A) clusters and 6894 APA genes, treated with silicon starvation and replenishment, were identified at nine time points. Significant APA was found in numerous genes (e.g. five cingulin genes) closely associated with the silicon‐starvation response, girdle bands and valve synthesis, suggesting that many genes participated in the responses to silicon availability and biosilica formation through changes in transcript isoforms. The poly(A) site usage profiles were distinct during various stages of silicon biomineralization responses. Moreover, a correlation between APA and expression levels of APA switching genes was also discovered. This is an interesting study that presents a genome‐wide profile of transcript ends in diatoms, which is distinct from that of higher plants, animals and other microalgae. This work provides an important resource to understand a different aspect of cell‐wall synthesis. Significance Statement: Although silicon plays an important role in the successful survival of diatoms due to its requirement in silicified cell walls, the post‐transcriptional regulation associated with the responses of diatoms to silicon availability is poorly understood. This work presents the uniqueness of an alternative polyadenylation profile that dynamically responds to silicon starvation and replenishment, indicating its potential contribution to post‐transcriptional regulation in biosilicification.